On the genus Hamma Buckton, 1905 (Hemiptera: Auchenorrhyncha) in Equatorial Africa, with descriptions of three new species - Durante, Antonio; Bayendi Loudit, Sandrine Mariella; Susini, Antonio (European Journal of Taxonomy, 2021)
As part of the classification of Membracidae from Gabon and Equatorial Guinea, a new species group of the genus Hamma Buckton, 1905 is proposed, and three new species are described: Hamma nigrum sp. nov., Hamma spinellii sp. nov. and Hamma caneparii sp. nov. An updated checklist and key to the genus Hamma are provided.